Pengaruh Sales Growth, Cash Flow, Cash Conversion Cycle dan Investment Opportunity Set terhadap Cash Holding - Nurhamidiyah, Nita; Utami, Tri (Universitas Pamulang, 2025)
This study aims to analyze the impact of sales growth, cash flow, cash conversion cycle, and investment opportunity set on cash holding. This type of research is quantitative research with an associative approach. The population in this study is property and real estate sector companies listed on the Indonesia Stock Exchange from 2019-2023. The sampling method used in this study is purposive sampling. Hypothesis testing is conducted using panel data regression with the help of EViews software. The results of the study indicate that simultaneously, the variables of sales growth, cash flow, cash conversion cycle, and investment opportunity set have an influence on cash holding. However, partially, sales growth, cash flow, and cash conversion cycle do not influence cash holding. Meanwhile, the structure of the investment opportunity set has an impact on cash holding.